Fusion as a mediator of cytolysis in mixtures of uninfected CD4+ lymphocytes and cells infected by human immunodeficiency virus. - Yoffe, B (1987)
We describe an unusual type of cytopathology in which uninfected CD4+ (helper/inducer) cells (cells expressing the human leukocyte antigen CD4) interact with cells persistently infected with the human immunodeficiency virus (HIV). Prior antigenic stimulation was not required, since CD4+ cells taken either from healthy persons without anti-HIV antibodies or from individuals with anti-HIV antibodies were capable of inducing cytolysis. Neither CD8+ (suppressor/cytotoxic) nor CD16+ (natural killer) cells mediated the reaction. Light microscopic and autoradiographic studies revealed that, prior to cytolysis, multinucleated giant cells were formed from fusions between HIV-infected cells and large numbers of uninfected CD4+ lymphocytes. These data may explain the paradox that exists in vivo in which a dramatic depletion of CD4+ lymphocytes occurs in the presence of a small number of HIV-infected CD4+ cells. These new insights into the pathogenesis of acquired immunodeficiency syndrome (AIDS) may lead to future therapeutic strategies.